Advances in agricultural economics - Kauffman, Kyle Dean (Advances in agricultural economic history ;, 2003)
Issues surrounding agriculture have always had pride of place among academic research in economic history. Interest in agricultural issues does not seem to come into fashion, and then fade into the background only to return years later. Indeed, agriculture was so vital to the workings of historical economies that a steady stream of important scholarship continues to be produced. Beyond its importance of being a record of the past, it is clear that much of the research in this area has important policy implications for both developed and developing economies. This type of work highlights an important facet of doing such historical research: learning from the past so as to understand better the world today. Several articles contained in volume two of Advances in Agricultural Economic History either implicitly or explicitly have lessons or policy implications for today. Volume 2 of Advances in Agricultural Economic History, like volume 1, contains important new work by both established and young academics. Additionally, this recent volume reflects, both geographically and methodologically, the broad scope of cutting edge work being done in this area. It is this type of scholarship that we seek to publish in future issues. We invite scholars who work in all areas of agricultural economic history to submit their work for publication in future volumes of Advances in Agricultural Economic History.